Emergency residential care settings: A model for service assessment and design. (February 2018) - Graça, João; Calheiros, Maria Manuela; Patrício, Joana Nunes; Magalhães, Eunice Vieira
Highlights: There is a marked need of research and evaluation on residential care settings. We test a framework for assessing a service model in residential emergency care. The framework addresses different focal areas, informants, and service components. Challenges for research and development on emergency residential care are discussed. Abstract: There have been calls for uncovering the "black box" of residential care services, with a particular need for research focusing on emergency care settings for children and youth in danger. In fact, the strikingly scant empirical attention that these settings have received so far contrasts with the role that they often play as gateway into the child welfare system. To answer these calls, this work presents and tests a framework for assessing a service model in residential emergency care. It comprises seven studies which address a set of different focal areas (e.g., service logic model; care experiences), informants (e.g., case records; staff; children/youth), and service components (e.g., case assessment/evaluation; intervention; placement/referral). Drawing on this process-consultation approach, the work proposes a set of key challenges for emergency residential care in terms of service improvement and development, and calls for further research targeting more care units and different types of residential care services. These findings offer a contribution to inform evidence-based practice and policy in service models of residential care.